Pelaksanaan Fungsi Case Management Untuk Meningkatkan Kendali Mutu dan Biaya Pelayanan Rawat Inap: Studi Fenomenologi di RSUD RAA Soewondo Pati - Nurhamdanah, Siti; Gero, Sabina (Yayasan Jompa Research and Development, 2025)
Background: Hospitals are healthcare institutions with complex systems and structures, involving various stakeholders ranging from managers, owners, payers, professional teams, to patients and families. In facing the challenges of service quality and financing efficiency, case management has become an important strategic intervention to ensure quality, integrated, and cost-effective care. Research Objective: To determine the implementation of case management functions in efforts to improve quality control and cost control of inpatient services at RAA Soewondo Pati Regional General Hospital. Research Method: This study employed a phenomenological qualitative method. Data collection was conducted through in-depth interviews with informants from various groups, namely PPA, DPJP, hospital management, health workers, case managers, and families/patients. Data analysis was conducted thematically using an interpretative approach. Research results: The implementation of the case manager function was not yet optimal, characterised by weak interprofessional coordination, overlapping roles, a lack of understanding of the role of the case manager, and the absence of a performance indicator-based evaluation system. Patients and families complained about ineffective service processes, including poor communication, long treatment durations, and a lack of education regarding follow-up care.